EXPLORING THE QUALITY OF STUDENTS' ARGUMENTATION IN MODEL ROCKETRY COMMUNITY OF INQUIRY - (:unkn) unknown (IATED-INT ASSOC TECHNOLOGY EDUCATION & DEVELOPMENT, 2011)
The purpose of this study is to develop a context in which students use their arguments on ill-structured problems and to explore the quality of the arguments developed by the students. Qualitative methods were used under situated learning perspective of social constructivism. Participants were 20 students in teacher education program in the section of physics education at a state university. The study took place in four stages: design and production of model rockets, administration of ill-structured qualitative questions, argumentation activities and administration of the same qualitative questions. Argumentation activities were recorded by three camcorders and all video records transcribed verbatim. These transcribed arguments analyzed as a case study. According to the research findings, the quality of the arguments was the third quality. A small percent of the arguments were first quality. Moreover, explanation and evidence types which the student used for their arguments were also analyzed. The results show the importance of argumentation activities. To develop skills of critical thinking and lifelong learning, argumentation activities can be used.
Keywords: Argumentation; ill-structured problems; quality of arguments; model rocketry; physics teaching; PROBLEM-SOLVING PROCESSES; QUESTION PROMPTS